Pengaruh Mini Vlog Dan Live Streaming Terhadap Minat Menginap Tamu Di Hotel Atanaya Kuta - Purnama, Jesslyn Lidya; Suarmana, I Wayan Restu; Semara , I Made Trisna (Institut Pariwisata dan Bisnis Internasional, 2025)
This study aims to measure the influence of mini vlogs and live streaming as digital marketing strategies on increasing guest interest in staying at the Atanaya Hotel Kuta. The research approach used was quantitative, with data collection methods through distributing questionnaires to potential guests and guests who had stayed at the Atanaya Hotel and were exposed to the mini vlog and live streaming content. The sample in this study consisted of 100 respondents selected using a purposive sampling technique. The obtained data were analyzed using multiple linear regression analysis to determine the magnitude of the influence of each independent variable on the dependent variable and to test the proposed hypotheses. The results showed that both mini vlogs and live streaming had a positive and significant effect on increasing guest interest in staying. This finding indicates that the effective use of interactive visual content through mini vlogs and live streaming can increase guest interest in the services and ambiance of the Atanaya Hotel. Based on these results, it is recommended that hotel management continue to develop authentic, engaging digital content that is consistent with the brand image to increase appeal and encourage potential guests to stay.